2016
DOI: 10.1159/000443936
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Mehran Score for Contrast-Induced Nephropathy after Transcatheter Aortic Valve Implantation in Patients with Aortic Stenosis

Abstract: Background/Aims: The Mehran risk score (MS) was adopted to predict the development of contrast-induced nephropathy (CIN) and includes clinical and procedural variables. In this study, we aimed to evaluate the value of MS in the prediction of CIN development after transcatheter aortic valve implantation (TAVI). Methods: Ninety-three patients (47 females; mean age, 77.2 ± 7.6 years) who underwent aortic valve replacement with TAVI for severe aortic stenosis in our center between June 2013 and November 2014 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…The ACEF score has previously been studied in patients undergoing TAVI, but most of these studies focused on predicting mortality from the ACEF score [21,22]. In addition, previously, some studies showed the relationship between increasing age and AKI development in TAVI patients [23], nevertheless, some studies revealed that there was no statistically significant relationship between age and AKI development [9,10,24]. Although low LVEF has previously been reported to be an important predictor of AKI development [23,24], Pyxaras et al indicated that low LVEF is not associated with the development of AKI after TAVI [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACEF score has previously been studied in patients undergoing TAVI, but most of these studies focused on predicting mortality from the ACEF score [21,22]. In addition, previously, some studies showed the relationship between increasing age and AKI development in TAVI patients [23], nevertheless, some studies revealed that there was no statistically significant relationship between age and AKI development [9,10,24]. Although low LVEF has previously been reported to be an important predictor of AKI development [23,24], Pyxaras et al indicated that low LVEF is not associated with the development of AKI after TAVI [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the utility of baseline, procedural characteristics or risk scores in predicting AKI following TAVI. These studies revealed that the development of AKI was closely associated with the patients' poor clinical outcome [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…7 The Mehran risk score (MRS) predicts the risk of developing CIN. 8 The MRS provides early detection of high-risk groups and has become the most widely used risk score for predicting CIN risk. 9,10 Risk factors include hypotension (systolic blood pressure <90 mm Hg, 5 points), application of intra-aortic balloon counterpulsation (5 points), severe heart failure, New York Heart Association grade III or IV or pulmonary edema (5 points), age !75 years (4 points), anemia (baseline hematocrit: female <36%, male <39%; 3 points), diabetes mellitus (3 points), contrast agent (1 point/100 mL), estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 (2,4,6 points are designated for an eGFR of 40 to 60, 20 to 40, and <20 mL/min/1.73 m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through a survey of 5,571 patients undergoing PCI, MRS system was designed by Mehran and the research team, which has been proved to be an effective method for CIN risk assessment. 6 It can detect high-risk groups of CIN early and has become the most extensively used risk score for forecasting CIN risk. 68 All patients were separated into four groups: low risk group (⩽5), moderate risk group (6-10), high risk group (11-15), very high risk group (⩾16).…”
Section: Introductionmentioning
confidence: 99%
“…6 It can detect high-risk groups of CIN early and has become the most extensively used risk score for forecasting CIN risk. 68 All patients were separated into four groups: low risk group (⩽5), moderate risk group (6-10), high risk group (11-15), very high risk group (⩾16). Risk factors include hypotension considered as systolic pressure <90 mmHg for one hour needing heart machine within 24 hours periprocedural (5 points), and serious heart failure (NYHA) Grade III/IV or a pulmonary edema) (5 points), application of intra aortic balloon counterpulsation (5 points), older than 75 (4 points), diabetes mellitus (3 points), the anemia is considered as baseline hematocrit <36% in women and <39% in men (3 points), contrast media (1 point for every 100 ml), estimated Glomerular Filtration Rate (eGFR)<60ml/min/1.73 m 2 (2, 4, 6 points was designated for 40-60, 20-40, <20).…”
Section: Introductionmentioning
confidence: 99%